Relação entre uso do esquema antirretroviral e aterosclerose coronariana em pacientes HIV positivos no estado de Sergipe - Oliveira, Débora Kelly Santos de (2021)
Antiretroviral therapy coincides with the change in the spectrum of the disease, increased life expectancy in patients with HIV/AIDS, and evidence of the occurrence of chronic cardiovascular diseases of atherosclerotic origin, when associated with long- term therapy. The objective was to evaluate the relationship between atherosclerosis and the use of an antiretroviral regimen in the treatment of HIV-positive patients and, secondarily, to quantify the calcium score in this group and to correlate the coronary calcium score and the duration of ART use. An observational, cross-sectional and analytical study of adult patients with HIV/AIDS, consecutively and non-randomly selected, asymptomatic from the cardiovascular point of view, from two reference services in outpatient care in the state of Sergipe: the Centro de Especialidades Physicians from Aracaju (CEMAR) and the University Hospital (HU) aged over 18 years and using antiretroviral therapy. In the statistical analysis, the following tests were used: Chi-square of adherence and Fisher's exact test, and p≤0.05 values were considered statistically significant. A confidence interval of 95% and an acceptable difference of about 10% were also considered. Atherosclerosis was defined as a calcium score greater than zero (CAC > 0). Traditional risk factors, metabolic syndrome and the Framingham score were analyzed. Of the sample, 32.1% were being followed up at CEMAR and 67.9% at HU, with a mean age of 46 years. 65.4% were male and 34.6% were female. 23.9% of the patients underwent all follow-up exams necessary for the analysis of the research, 64.15% ET and ECHO and 43.9% TC. 22.64% of patients had CD4 ≤ 350 and the VC of HIV+ patients was undetectable. 96.36% females and 86.54% males were classified based on the Framingham score as low risk. 36.48% had been on ART for more than 10 years and had been on ART for an average of 72 months. This study showed a low prevalence of atherosclerosis in patients with HIV/AIDS using antiretroviral therapy for at least two years. Among the risk factors evaluated, age, time of use and therapeutic class were related. The results show an association between ART containing Protease Inhibitors, although they are potent drugs to improve clinical outcomes, preventing viral replication and decreasing viral load, but the excessive cardiovascular risk is related to long-term exposure, for which PIs can promote atherosclerosis can be detected by cardiac computed tomography. And the prevalence of atherosclerosis by the Calcium Score in patients living with HIV documented around 40%, represented 31.17% of the sample studied with atherosclerotic involvement. The p values were considered statistically significant in 100% of the variables analyzed and the challenge is to promote the prevention of cardiovascular risks to reduce the number of coronary events, and the profile traced with this collection will allow a more careful approach to these patients, especially in the character preventive care with HIV/AIDS patients in the state of Sergipe.